The Effect of Profitability, Liquidity and Financing Risk on Murabahah Financing at Islamic Commercial Banks in Indonesia (2009-2020 Period) - Rima Yusnita; Hendri Andi Mesta (Financial Management Studies, 2021)
In general, Islamic banks with conventional banks are different. The difference is in the operating base used. Conventional banks operate on interest, while Islamic banks operate on profit sharing, buying and selling and leasing. The main activity of the bank is to channel funds to the public. The distribution of these funds in conventional banks is called credit, while in Islamic banks it is more often referred to as financing. Of the 8 types of financing that, murabahah financing is the financing that is most in demand by the public and has the highest value every year. The purpose of this study was to determine the effect of Return On Assets, Financing to Deposit Ratio and Non Performing Financing on murabahah financing at Islamic Commercial Banks in Indonesia for the 2009-2020 period. The population in this study are Islamic commercial banks in Indonesia in 2009-2020. The sampling technique used purposive sampling method and obtained 10 banks with a total sample of 107 samples. The research data uses secondary data taken from the official website of each bank, and the research method used is multiple linear regression with a significance level of 5%. The results of this study indicate that the Return On Assets and Financing to Deposit Ratio variables have no effect on murabahah financing and Non-Performing Financing has a significant positive effect on murabahah financing at Islamic commercial banks. For further researchers, it is expected to include all Islamic banking and add variables and research samples.